2019
DOI: 10.1149/2.0661908jes
|View full text |Cite
|
Sign up to set email alerts
|

Microhardness Improvement of Ni-W/SiC Composite Coatings by High Frequency Induction Heat Treatment

Abstract: Electrodeposited Ni-W alloy coating is considered as one of the most suitable candidate to replace the environmentally hazardous hexavalent hard chromium coatings. However, it is necessary to carry out heat-treatment at a high temperature to improve its microhardness and refine its grain. In the present work, an alternative high frequency induction heat-treatment (HFI-HT) technology was used to improve surface microhardness of Ni-W/SiC composite coatings, which were electrodeposited from an ammonium-citrate ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…Before electrodeposition, the substrate was polished by different grades of emery papers, activated by immersing in HCl solution (15%) for 15 s and then cleaned with de-ionized water. The electrodeposition parameters and the composition of electrolytes used in this paper are similar to many literature ( Ref 1,4,16,21) and listed in Table 1. The trisodium citrate was applied as complexing agent, and no surfactants were added into the electrolyte.…”
Section: Materials and Preparationmentioning
confidence: 88%
“…Before electrodeposition, the substrate was polished by different grades of emery papers, activated by immersing in HCl solution (15%) for 15 s and then cleaned with de-ionized water. The electrodeposition parameters and the composition of electrolytes used in this paper are similar to many literature ( Ref 1,4,16,21) and listed in Table 1. The trisodium citrate was applied as complexing agent, and no surfactants were added into the electrolyte.…”
Section: Materials and Preparationmentioning
confidence: 88%
“…WC has been synthesized in situ by laser cladding, improving the properties of Ni coating and Co alloy coating [10,11]. Su et al [12] found that the high-frequency induction heat treatment of Ni-W alloy coating yielded Ni 4 W and Ni 6 W 6 C precipitates, achieving a 1100 Hv coat hardness. Lee et al found that Ni 4 W and Ni 6 W 6 C were obtained by irradiating Ni-W alloy at room temperature and annealing at 850 • C [13].…”
Section: Introductionmentioning
confidence: 99%
“…The Ni–W co‐deposition technology was developed to resolve this dilemma. It was found that the co‐deposition of various micro/nanoparticles such as Si 3 N 4 , [ 10 ] Al 2 O 3 , [ 11 ] SiC, [ 12,13 ] ZrO 2 , [ 14–18 ] TiN, [ 19–21 ] TiB 2 , [ 22 ] diamond, [ 23 ] and multi‐walled carbon nanotubes (MWCNTs) [ 24,25 ] with the Ni–W alloy matrix can significantly enhance the mechanical properties and the corrosion resistance of the coating.…”
Section: Introductionmentioning
confidence: 99%